The Phenomenon of Feudalism in Islamic Boarding Schools: Examining the Social Structure of the Relationship between Kiai and Santri at the Ainul Yaqin Campus Islamic Boarding School - Miftahul Jannah; Silvia Khodrotun Nada; Maskuri Bakri (Al-Ulum: Jurnal Pendidikan Islam, 2026)
This article departs from the accusations of some people who consider that the social system in Islamic boarding schools reflects the practice of feudalism. This article aims to examine and uncover the existing reality, around the relationship between kiai and students through a case study at the Ainul Yaqin Campus Islamic Boarding School, University of Islam Malang. The research was carried out with direct observation, documentation and in-depth interviews with administrators and students. The results of the study show that the leadership style of the kiai in this Islamic boarding school is democratic and not based on heredity, while the relationship between kiai and students is built on the basis of science, example, and spiritual awareness. Practices such as solemnity and respect for students do not reflect the dominance of power, but the value of education that is rooted in Islamic manners and traditions. Therefore, social relations in this Islamic boarding school cannot be categorized as feudal, but as part of an education system that is full of moral and religious meaning.